2020
DOI: 10.1094/pdis-08-19-1676-re
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma Isolates Inhibit Fusarium virguliforme Growth, Reduce Root Rot, and Induce Defense-Related Genes on Soybean Seedlings

Abstract: Sudden death syndrome (SDS) caused by Fusarium virguliforme is among the most important diseases affecting soybean in the United States. The use of biological control agents (BCAs) such as Trichoderma spp. can be a valuable resource to suppress F. virguliforme populations. Therefore, this research focused on screening possible BCAs against F. virguliforme and evaluating mycoparasitism and the induction of systemic resistance as mechanisms underlying the antagonistic activity of selected BCAs against F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 53 publications
1
21
0
2
Order By: Relevance
“…Notably, ecological guilds belonging to the “pathotrophic mode” differed in abundance between tillage treatments; the abundance of “mycoparasites,” and “animal pathogens” increased, whereas that of “plant pathogens” declined in no-till soils. The turnover caused by tillage is in line with other studies indicating a positive correlation between the occurrence of AMF and mycoparasites often favored in carbon rich soil ( Veach et al, 2018 ; Pimentel et al, 2020 ). However, the relatively high abundance of plant pathogens in tilled soils is not consistent with other studies ( Steinkellner and Langer, 2004 ; Degrune et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…Notably, ecological guilds belonging to the “pathotrophic mode” differed in abundance between tillage treatments; the abundance of “mycoparasites,” and “animal pathogens” increased, whereas that of “plant pathogens” declined in no-till soils. The turnover caused by tillage is in line with other studies indicating a positive correlation between the occurrence of AMF and mycoparasites often favored in carbon rich soil ( Veach et al, 2018 ; Pimentel et al, 2020 ). However, the relatively high abundance of plant pathogens in tilled soils is not consistent with other studies ( Steinkellner and Langer, 2004 ; Degrune et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…Trichoderma spp. have been studied commonly because of its ability to inhibit soil-borne pathogens and have good plant defense responses (Papavizas, 1985;Hermosa et al, 2012;Pimentel et al, 2020). In this study, PCR-DGGE results showed significant shifts in Trichoderma community in the rhizosphere of R. pseudostellariae after extended monoculture ( Supplementary Figure 2 and Figure 2).…”
Section: Discussionmentioning
confidence: 66%
“…This symbiotic relationship can effectively protect the plant from pathogens (Mukherjee et al, 2018;Galletti et al, 2020). When Trichoderma interacts with plants, it induces the expression of genes involved in the defense responses of plants (Brotman et al, 2013;Mayo et al, 2016;Manganiello et al, 2018;De Palma et al, 2019;Pimentel et al, 2020) and promotes plant growth and root development (Hermosa et al, 2012). However, the role of root-associated mutualistic plant symbiont, Trichoderma spp., in activation of R. pseudostellariae immunity by triggering the expression of defense-related genes is never explored.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these properties, various investigations have evaluated the use of BCAs and their mode of action for the control of SDS. For example, Trichoderma harzianum and two arbuscular mycorrhizal fungus (AMF), Rhizophagus irregularis and R. intraradices , reduced SDS severity caused by F.v 78‐80 . On the other hand, plant growth‐promoting bacteria (PGPB) also proved to be effective in controlling SDS‐causing Fusarium species.…”
Section: Biological Controlmentioning
confidence: 99%
“…Regarding the mode of action, both T. harzianum and Lysobacter enzymogenes strain C3 directly suppress F.v . mycelial growth 78,82 . Additionally, T. harzianum induces the activation of defense responses in soybean plants, increasing the expression of defense‐related genes associated with the salicylic acid (SA) and jasmonic acid/ethylene (JA/ET) pathways.…”
Section: Biological Controlmentioning
confidence: 99%